2015
DOI: 10.1007/s10444-015-9421-4
|View full text |Cite
|
Sign up to set email alerts
|

Reduced models for sparse grid discretizations of the multi-asset Black-Scholes equation

Abstract: This work presents reduced models for pricing basket options with the Black-Scholes and the Heston model. Basket options lead to multi-dimensional partial differential equations (PDEs) that quickly become computationally infeasible to discretize on full tensor grids. We therefore rely on sparse grid discretizations of the PDEs, which allow us to cope with the curse of dimensionality to some extent. We then derive reduced models with proper orthogonal decomposition. Our numerical results with the Black-Scholes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…The POD with Galerkin projection is the most known and frequently used reduced-order modeling method. POD based reduced-order modeling is investigated for pricing European option and American option wherein different from European option there exist variational inequalities [5,30,31] to be handled, under Black-Scholes and Heston model [2,4,20,21]. Reduced-order models based on POD are optimal in terms of energy content.…”
Section: Introductionmentioning
confidence: 99%
“…The POD with Galerkin projection is the most known and frequently used reduced-order modeling method. POD based reduced-order modeling is investigated for pricing European option and American option wherein different from European option there exist variational inequalities [5,30,31] to be handled, under Black-Scholes and Heston model [2,4,20,21]. Reduced-order models based on POD are optimal in terms of energy content.…”
Section: Introductionmentioning
confidence: 99%
“…Further, the resulting non-linear truncated problem has been solved by a semiimplicit FEM. In [43], Peherstorfer et al suggested reduced models for pricing basket options with the Black-Scholes and the Heston models. Shcherbakov [48] extended the operator splitting formulation to the radial basis function partition of unity method.…”
Section: Introductionmentioning
confidence: 99%
“…However, little attention has been paid to applications in finance. Recent work on model reduction techniques in finance with a primary focus on POD methods include, e.g., [58,56,57,49,46]. First results for RBM can be found in [16,48,49].…”
Section: Introductionmentioning
confidence: 99%